The evolution of aggressive and amicable play fighting in primates: a phylogenetic perspective. Issue 1 (2nd January 2023) - Pellis, S. M.; Pellis, V. C.; Ham, J. R.
ABSTRACT: Play fighting involves competing for an advantage, which can be derived from behavior typical of conspecific aggression, predation, sexual and other affinitive contexts. Here the phylogenetic distribution of aggressive play fighting (involving biting) and amicable play fighting (involving grooming and mounting) in juveniles of 48 species of primates was analyzed. Both aggressive and amicable play fighting were likely equally present in ancestral primates, and then some lineages either maintained that pattern or exaggerated the use of one type relative to the other. In species engaging in both types of play, the ancestral pattern is for them to remain distinct, with sequences of one type not transforming into sequences of the other type. In two genera, mixing types of play was exaggerated, with rapid bidirectional transitions between aggressive and amicable play. These findings suggest that different types of play evolved independently and their combination is a secondarily evolved, derived state.